2021
DOI: 10.1186/s12968-021-00729-0
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial 4D flow cardiovascular magnetic resonance: a reproducibility study in sinus rhythm and atrial fibrillation

Abstract: Background Four-dimensional (4D) flow cardiovascular magnetic resonance (CMR) allows sophisticated quantification of left atrial (LA) blood flow, and could yield novel biomarkers of propensity for intra-cardiac thrombus formation and embolic stroke. As reproducibility is critically important to diagnostic performance, we systematically investigated technical and temporal variation of LA 4D flow in atrial fibrillation (AF) and sinus rhythm (SR). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 41 publications
4
20
0
Order By: Relevance
“…CMR examinations were performed on 3T MRI systems (Verio syngo MRB17 or MAGNETOM Prisma VE11C, both Siemens, Germany). LA flow characteristics were assessed using ECG-gated time-resolved 3D phase-contrast CMR with 3-directional velocity encoding imaging (‘4D flow’), using a post-processing tool which we have recently validated 9 and made available on the Oxford University Research Archive platform ( https://doi.org/10.5287/bodleian:ey4ovzdbB ). Briefly, data analysis included 3D segmentation of LA volume, and determination of two sets of parameters ( Figure 1 ): firstly, LA peak and mean velocities, since low atrial velocities are thought to be linked to activation of the coagulation cascade with increased red blood cell and plasma protein aggregation 1 ; secondly, ‘rotational’ flow parameters, since the normal flow pattern within the LA is characterized by vortexes, 10 and disruption of vortical flow is associated with altered shear stress and platelet adhesion and aggregation in computational and silicone replica models of intra-cardiac blood flow.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…CMR examinations were performed on 3T MRI systems (Verio syngo MRB17 or MAGNETOM Prisma VE11C, both Siemens, Germany). LA flow characteristics were assessed using ECG-gated time-resolved 3D phase-contrast CMR with 3-directional velocity encoding imaging (‘4D flow’), using a post-processing tool which we have recently validated 9 and made available on the Oxford University Research Archive platform ( https://doi.org/10.5287/bodleian:ey4ovzdbB ). Briefly, data analysis included 3D segmentation of LA volume, and determination of two sets of parameters ( Figure 1 ): firstly, LA peak and mean velocities, since low atrial velocities are thought to be linked to activation of the coagulation cascade with increased red blood cell and plasma protein aggregation 1 ; secondly, ‘rotational’ flow parameters, since the normal flow pattern within the LA is characterized by vortexes, 10 and disruption of vortical flow is associated with altered shear stress and platelet adhesion and aggregation in computational and silicone replica models of intra-cardiac blood flow.…”
Section: Methodsmentioning
confidence: 99%
“…the tendency of flow to rotate by using the area under the vorticity–time curve over the averaged cardiac cycle using volume-weighted vorticity measures, in radians). 9 The equations used for calculating the LA 4D flow parameters are available on the Oxford University Research Archive platform at the following link: https://doi.org/10.5287/bodleian:ey4ovzdbB . All data were acquired using a 4D flow sequence with retrospective gating except for one participant where a prospectively gated sequence was used.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the limited spatial resolution of 4D flow MRI may not satisfy the minimum number of voxels needed to segment the LAA accurately and reliably in a certain number of cases [6]. In a recent study, reliability and reproducibility of 4D flow parameters in AF patients were reported [60]. Left atrial peak velocity Four-Dimensional Flow Magnetic Resonance Imaging and Applications in Cardiology DOI: http://dx.doi.org/10.5772/intechopen.99362 and vorticity were found to be more reproducible and independent of physiological factors than mean velocity, vortex volume and stasis.…”
Section: Mitral Regurgitation the Presented Case Has Mitral Thickening With Evidence Of Cleft In The Anterior Mitral Leaflet Panel A Showmentioning
confidence: 99%